(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Consumption Expenditure of the Government is estimated atRs. 1459026 lakh in 2011-12 (B.E.) as against Rs. 1456753 lakh in 2010-11(R.E.) and Rs. 1170360 lakh in 2009-10. The consumption expenditure of theGovt. is estimated to increase by 0.16 percent in 2011-12 (B.E.) over 2010-11(R.E.) whereas it increases by 24.47 percent in 2010-11 (R.E.) over 2009-10. Gross Capital Formation i.e. investment on buildings,roads & other constructions, purchase of vehicles and machinery &equipment by Administrative Departments and Departmental CommercialUndertakings is estimated at Rs. 425441 lakh in 2011-12 (B.E.) as against Rs.374245 lakh in 2010-11 (R.E.) and Rs.357125 lakh in 2009-10 showing an increaseof 13.68 percent in 2011-12 (B.E.) over 2010-11 (R.E.) where as it increased by4.79 percent in 2010-11 (R.E.) over 2009-10. Current transfers which also include subsidies and interestpayments are estimated at Rs. 1484599 lakh in 2011-12 (B.E.) as against Rs.1312149 lakh in 2010-11 (R.E.) and Rs. 1013508 lakh in 2009-10. It indicatesthat current transfers are likely to increase by 13.14 percent in 2011-12(B.E.) over 2010-11 (R.E.) whereas this increase was 29.47 percent in 2010-11(R.E.) over 2009-10.